The Development of a Web Portal for an Assisted Reproduction Center in South India and an Analysis of its Efficacy (Medico Legal Update, 2019)
Introduction: Telemedicine is the need of the hour to keep pace with developments in the healthcare industry. Easy and better access to facilities facilitates customer retention. Online consultations facilitate hassle free patient–doctor communication, in sharp contrast with the common sight of long waiting queues for doctors. Objective: To develop and analyse the efficacy of a web portal for an assisted reproduction center at a tertiary care hospital in South India.Method: This study was conducted between November 2017 and April 2018. An initial study was conducted to analyse the need for online consultations at this center. Based on this study and considering the future requirements of e consultation in Kasturba hospital, a web portal was developed. Upon the completion and implementation of the web portal, patients who registered for the web portal services were administered a feedback questionnaire on the efficacy of the web portal. This questionnaire had to be filled out by the patients when they logged out of their web portal account. The questionnaire responses were analysed to assess the acceptance level of patients to online consultation and the working efficiency of the web portal.Results: Patients who registered with the web portal found it user friendly. They found it easy to access all information on the portal. The positive feedback and suggestions from patients suggest that the patient portal was wilfully accepted by them.